Physical Agents and RFID for the implementation of the Shop Floor Control on a Distribution Centre. - Javier de las Morenas; Andrés García; Fernando Martínez; Pablo García Ansola (Revista Iberoamericana de Automática e Informática Industrial RIAI)
The application of the multi-agent systems technology for shop-floor control has generated great expectations among professionals and researchers in the last decade. The use of this technology conveys, by the definition of the agents, reactive systems (able to respond to changes), proactive systems (their behavior is oriented towards the achievement of predefined objectives), autonomy, and social skills (consensual decision making), causing the emergence of many initiatives. Unfortunately, most references on this field are mainly concerned with: the definition of agents, statements of intent, simulations or rather ambitious proposals; which prevents industry from adopting this technology.